Energy efficiency: case study in Rio Grande do Sul agribusiness (Research, Society and Development, 2020)
The issue of energy efficiency is current, relevant and present in the discussions of the world energy system, impacting several business segments. This research aims to carry out an energy efficiency study at the plant of an agribusiness located in the southern region of the state of Rio Grande do Sul. As for the methodological development, the present study has its approach with quantitative characteristic, because the numerical data are preponderant; as procedures, descriptive and case study, for describing the characteristics of a cereal enterprise and, because it is an analysis of a venture with unique characteristics, not allowing the results achieved to be generalized; and for data collection and analysis, documentary research, field survey and spreadsheet. Also presented were documentary analysis of energy bills, analysis of electric motors, luminotechnical analysis and loss analysis in transformers. With the energy efficiency study completed it was possible to identify in the electrical equipment and in the electric bills the possibility of reduction in the annual energy consumption of 8.97%.